Implementation of Hazard Analysis and Critical Control Points for "B'Bananas" Fried Banana Snacks at a Small Business in Surabaya, Indonesia - A.R. Yelvia Sunarti; Annisa Kurnia Pratiwi; Sultan Tora Fattahu Majid; Erwan Adi Saputro (Nusantara Science and Technology Proceedings, 2023)
A food safety management system based on the principles of hazard analysis and critical control points (HACCP) is a common method used to help businesses identify and control the broad spectrum of food safety hazards. To ensure food quality and safety, analysis is required to address hazards during the production process. Fried banana is a snack food that is widely found. It is made from bananas that have been peeled. The bananas are cut into pieces as desired then coated with a thick batter made from a mixture of flour, a little salt, and sugar, then fried in hot oil. then the bananas are coated with vanilla, chocolate, green tea, tiramisu, and cappuccino. and toppings including milo, oreo, cheese, red velvet, and peanuts. This study was conducted to identify and minimize hazards during the production process of B’Bananas (one of the traditional foods) and provide recommendations for establishing a Hazard Analysis Critical Control recommendation to build a Hazard Analysis Critical Control Point (HACCP) system. In the HACCP analysis, it was found that the main factor that most influences is the biology of the material because the product is a wet product that must have special handling and there cannot be bacterial contamination because it will be consumed by humans. if there is a contamination from the raw material or during the manufacturing process it will cause a fatal effect on human health and will endanger consumers. Therefore, the control of materials and processes must be improved by minimizing the stockpiling of raw materials not to expire and the use of sterile cooking equipment.